Mlečki (rod Euphorbia) Slovenije - Frajman, Božo (Scopolia, 2007)
The study presents the results of revision regarding the genus Euphorbia in Slovenia. On the basis of the revision of available herbarium material, the occurrence of 28 Euphorbia species was confirmed (out of 36 listed in different literature sources) and two new species were found - Euphorbia taurinensis All. and E. myrsinites L. The data on taxa distribution in Slovenia and its neighbouring countries, as well as their ecology and phenology were gathered. On the basis of literature, herbarium revision and field work, distribution maps of the studied species were produced. Suggestions for nature conservation and protection of some of them were also proposed. Furthermore, determination key for euphorbias growing in Slovenia was compiled.
Keywords: botanika; Rhododendron-Park Bremen; fenologija; Euphorbia; mlečki; Slovenia; Slovenija